Interventional Radiology Management of the Acute Trauma Patient - Zane, Kylie; Prakash, Priya; Zangan, Steven M.; Lorenz, Jonathan M. (Digestive Disease Interventions, 2025)
The management of traumatic injuries requires the coordinated efforts of a multidisciplinary team of trauma surgeons, subsurgical specialties, intensivists, and interventionalists. The interventional radiologist plays a critical role in the management of acute trauma by offering 24-hour consultation, expert imaging interpretation, and an array of life-saving minimally invasive procedures. As integrated members of the multidisciplinary clinical team, the interventional radiologist should be able to review clinical information, communicate clearly with consulting services, perform timely intervention, provide postprocedural follow-up, and document relevant information in the patient chart. The following review provides a stepwise approach to the rapid clinical assessment of the trauma patient and outlines the pathways taken by the trauma patient to the interventional radiology suite.
Keywords: trauma; hemodynamic instability; interventional radiology